Droop Control Strategy for Voltage Source Converters Containing Renewable Power Sources - Andrade Aguero, Ivan Eric; Peña, Rubén; Blasco-Gimenez, Ramón; Riedemann, Javier; Pesce, Cristian (My University, 2020)
This paper presents a strategy to control the active and reactive power in the point of common connection (PCC) of a wind generation system operating in islanded mode. A full back-to-back voltage source converter (VSC) is connected between each wind generator and the PCC. The control scheme considers voltage and frequency regulation for each VSC. The voltage and frequency references are obtained from P-V and Q-f droop characteristics of the generators, where Q and P are the reactive and active power supplied by each VSC to the PCC. Proportional-integral (PI) controllers process the voltage and frequency errors and set reference currents (in d-q frame) to be imposed by the converter. The strategy has been validated by mean of simulations, and results are presented showing the performance of the control strategy proposed.
Keywords: droop control; renewable energy